STUDI ETNOBOTANI TUMBUHAN OBAT YANG DIMANFAATKAN DI DESA BANI AMAS KECAMATAN BENGKAYANG KABUPATEN BENGKAYANG - tianti, Kris; Oramahi, H.A.; Yanti, Hikma (JURNAL HUTAN LESTARI, 2013)
West Kalimantan is famous for wet tropical forests that store different types of plant species that are traditionally used by the public. Bani Amas Village Community is still very dependent on the forest for their daily needs, especially in the use of medicinal plants to cure various diseases has been done for generations and has been going on since long. The purpose of this study is to determine the types of medicinal plants and their use by the public, knowing the medicinal plant parts used, how mixes and know the different types of diseases that can be overcome by using the herb. From the research found 48 medicinal plant species, 46 genera and 34 families were used, as many as 17 species in the form of herbs, 35 species used alone, 26 species the leaves are used, 24 species used by boiling, 35 species used by drink. Keywords : Ethnobotany, medicinal plants, Bani Amas village.